Development of Accounting Theories Specific to the National Accounting Literature of the First Half of Twentieth Century - Sorin Damian (EIRP Proceedings, 2011)
Need to identify plausible explanations of the principles underlying the double entry accountingover time determined by various manifestations of thought that have resulted in many theories. All thesetheories have proposed to explain and substantiate dopic formalism, but many of them no longer a valuetoday than a purely historical perspective. The representative of such theories has been many pages writtenRomanian and foreign authors in the first half of the twentieth century. Some Romanian authors mention theIoan E. Evian, D. Voina, CG Demetrescu, S. Iacobescu, Al. Sorescu, C. Pantu, C. Petrescu, Grigore-TrancuIaşi and others. Bibliography time accounting theories shared accounts: embryos of theories and scientifictheories.